Peptidoglycan Switches Off the TLR2-Mediated Sperm Recognition and Triggers Sperm Localization in the Bovine Endometrium - Elesh, Ibrahim Fouad; Marey, Mohamed Ali; Zinnah, Mohammed Ali; Akthar, Ihshan; Kawai, Tomoko; Naim, Fayrouz; Goda, Wael; Rawash, Abdel Rahman A.; Sasaki, Motoki; Shimada, Masayuki; Miyamoto, Akio (Frontiers in Immunology, 2021)
In mammals, the uterine mucosal immune system simultaneously recognizes and reacts to most bacteria as well as allogenic sperm mainly through the Toll-like receptors (TLR)2/4 signaling pathway. Here, we characterized the impact of pathogen-derived TLR2/4 ligands (peptidoglycan (PGN)/ lipopolysaccharide (LPS)) on the immune crosstalk of sperm with the bovine endometrial epithelium. The real-time PCR analysis showed that the presence of low levels of PGN, but not LPS, blocked the sperm-induced inflammatory responses in bovine endometrial epithelial cells (BEECs) in vitro. Immunoblotting analysis revealed that PGN prevented the sperm-induced phosphorylation of JNK in BEECs. Activation or blockade of the TLR2 system in the endometrial epithelium verified that TLR2 signaling acts as a commonly-shared pathway for PGN and sperm recognition. The impairment of endometrial sperm recognition, induced by PGN, subsequently inhibited sperm phagocytosis by polymorphonuclear neutrophils (PMNs). Moreover, using an ex vivo endometrial explant that more closely resembles those in vivo conditions, showed that sperm provoked a mild and reversible endometrial tissue injury and triggered PMN recruitment into uterine glands, while PGN inhibited these events. Of note, PGN markedly increased the sperm attachment to uterine glands, and relatively so in the surface epithelium. However, addition of the anti-CD44 antibody into a PGN-sperm-explant co-culture completely blocked sperm attachment into glands and surface epithelia, indicating that the CD44 adhesion molecule is involved in the PGN-triggered sperm attachment to the endometrial epithelium. Together, these findings demonstrate that, the presence of PGN residues disrupts sperm immune recognition and prevents the physiological inflammation induced by sperm in the endometrial epithelium via the MyD88-dependent pathway of TLR2 signaling, possibly leading to impairment of uterine clearance and subsequent embryo receptivity.